Structure-Property Relationships in Non-Linear Optical Crystals II The IR Region - Wu, Xin-Tao.; Chen, Ling.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Xiao-Ming Jiang, Sheng-Ping Guo, Hui-Yi Zeng, Ming-Jian Zhang, Guo-Cong Guo: Large Crystal Growth and New Crystal Exploration of Mid-Infrared Second-Order Nonlinear Optical Materials. Kechen Wu: Simulation and Design of Infrared Second-Order Nonlinear Optical Materials in Metal Cluster Compounds Chaoyang Tu: The Recent Development Of SRS and SRS SF- conversion Laser Crystal Hua-Jun Zhao, Xin-Tao Wu, Li-Ming Wu: Exploration of New Second-Order Nonlinear Optical Compounds Containing Main Group Elements
Xiao-Ming Jiang, Sheng-Ping Guo, Hui-Yi Zeng, Ming-Jian Zhang, Guo-Cong Guo: Large Crystal Growth and New Crystal Exploration of Mid-Infrared Second-Order Nonlinear Optical Materials -- Kechen Wu: Simulation and Design of Infrared Second-Order Nonlinear Optical Materials in Metal Cluster Compounds -- Chaoyang Tu: The Recent Development Of SRS and SRS SF- conversion Laser Crystal -- Hua-Jun Zhao, Xin-Tao Wu, Li-Ming Wu: Exploration of New Second-Order Nonlinear Optical Compounds Containing Main Group Elements.
Keywords: Chemistry; Chemistry, inorganic; Optical materials; Chemistry; Inorganic Chemistry; Optics, Optoelectronics, Plasmonics and Optical Devices; Optical and Electronic Materials